Structural, electronic and magnetic properties of Fe2TiP full-Heusler compound: A first-principles study - Reza Sarhaddi (Progress in Physics of Applied Materials)
This study examined the electronic, magnetic, and structural properties of Fe2TiP full-Heusler compound, using the pseudo-potential plane wave (PP-PW) formalism based on density functional theory (DFT). Energetically, the AlCu2Mn-type structure of Fe2TiP had greater stability in comparison with the CuHg2Ti-type structure and show the half-metallic (HF) ferrimagnetic behavior. Based on the results at the lattice constant of 5.65 Å, the total magnetic moment (Mtot) was 1 μB/unit cell; this finding is consistent with the Slater-Pauling (SP) rule. The minority spin band exhibited a semiconductor behavior (spin-flip gap of 0.21 eV; gap of 0.35 eV), whereas the majority spin band was metallic. The origin of half-metallicity and appearance of the minority band gap were discussed using the band structure calculations and density of states (DOS). In addition, dependence of magnetic properties on the lattice constant was evaluated. In the lattice constant range of 5.55-5.85 Å, the Fe2TiP compound can retain the half-metallicity. Therefore, the half-metallic feature was not influenced by the lattice distortion, and this material seems to have potential applications in future spintronics devices.